Immune inactivation by APOBEC3B enrichment predicts response to chemotherapy and survival in gastric cancer. (1st January 2021) - Xia, Siyu; Gu, Yun; Zhang, Haijian; Fei, Yuchao; Cao, Yifan; Fang, Hanji; Wang, Jieti; Lin, Chao; Zhang, Heng; Li, He; He, Hongyong; Xu, Jiejie; et al.
ABSTRACT: Apolipoprotein B mRNA editing enzyme catalytic polypeptide 3B (APOBEC3B) plays an important role in tumor mutagenesis. However, its clinical significance in gastric cancer (GC) remains largely unknown. We enrolled a total of 482 GC patients from Zhongshan Hospital, Fudan University for immunohistochemistry (IHC) staining to evaluate the prognostic and predictive values of APOBEC3B. Genomic and phenotypic datasets from the Cancer Genome Atlas (TCGA) and Asian Cancer Research Group (ACRG) cohort were downloaded for external validation and complementary bioinformatic analysis. Fresh specimens of additional 60 patients from Zhongshan Hospital, Fudan University were collected to detect CD8 + T cell phenotype with flow cytometry (FCM). The high expression of APOBEC3B indicated inferior overall survival (OS, P < .001 and P = .003) and disease-free survival (DFS, P < .001 and P < .001), yet superior therapeutic responsiveness to fluorouracil-based adjuvant chemotherapy (ACT) in TNM stage II patients. The tumor microenvironment (TME) of APOBEC3B-enriched tumors was characterized by reduced infiltration of tumor reactive CD8 + T cells expressing both effector molecules and immune checkpoints. APOBEC3B high CD8 + T cell high GC patients were most likely to benefit from ACT and PD-1 blockade. Our study demonstrates that APOBEC3B was an independent prognostic and predictive factor in GC. The potential interplay between APOBEC3B and CD8 + T cells merited further investigations.